Phage display revisited: Epitope mapping of a monoclonal antibody directed against Neisseria meningitidis adhesin A using the PROFILER technology. Issue 4 (18th May 2016) - Cariccio, Veronica Lanza; Domina, Maria; Benfatto, Salvatore; Venza, Mario; Venza, Isabella; Faleri, Agnese; Bruttini, Marco; Bartolini, Erika; Giuliani, Marzia Monica; Santini, Laura; Brunelli, Brunella; Norais, Nathalie; et al.
ABSTRACT: There is a strong need for rapid and reliable epitope mapping methods that can keep pace with the isolation of increasingly larger numbers of mAbs. We describe here the identification of a conformational epitope using Phage-based Representation OF ImmunoLigand Epitope Repertoire (PROFILER), a recently developed high-throughput method based on deep sequencing of antigen-specific lambda phage-displayed libraries. A novel bactericidal monoclonal antibody (mAb 9F11) raised against Neisseria meningitidis adhesin A (NadA), an important component of the Bexsero ® anti-meningococcal vaccine, was used to evaluate the technique in comparison with other epitope mapping methods. The PROFILER technology readily identified NadA fragments that were capable of fully recapitulating the reactivity of the entire antigen against mAb 9F11. Further analysis of these fragments using mutagenesis and hydrogen-deuterium exchange mass-spectrometry allowed us to identify the binding site of mAb 9F11 (A250-D274) and an adjoining sequence (V275-H312) that was also required for the full functional reconstitution of the epitope. These data suggest that, by virtue of its ability to detect a great variety of immunoreactive antigen fragments in phage-displayed libraries, the PROFILER technology can rapidly and reliably identify epitope-containing regions and provide, in addition, useful clues for the functional characterization of conformational mAb epitopes.